A case of isolated meningitis caused by Bartonella henselae - Maria Del Pilar Morel Almonte; Jose Guillermo Castro (IDCases)
Central nervous manifestations of bartonella infection are uncommon and can vary from encephalitis, meningitis, nerve palsy as well as ocular involvement. Most of these manifestations are described in immunocompromised individuals. We report a case of a previously healthy 42-year-old male who presented to the hospital with 4-weeks of fever and headache and found with meningeal signs on physical exam. He reported been scratched by a stray cat at work some days before his symptoms started. He remained febrile in the hospital. Initial work up was unrevealing, but CSF analysis showed pleocytosis, elevated protein and low CSF glucose- plasma glucose ratio consistent with CNS bacterial infection. Blood and CSF cultures were negative. Bartonella henselae titers in serum were found to be elevated. No other source of infection was identified. Patient was diagnosed with isolated aseptic meningitis secondary to Bartonella henselae infection. Treatment with doxycycline and rifampin was started with good response and resolution of symptoms.